A Comparative Evaluation of PID and Lead-Lag Controllers in an AVR-PSS Coordination - Soniya Karki,; Bivek Kumar Mallik,; Rajiv Pandit,; Rohit Kumar Shah,; Nutan Raj Pathak, (Journal of Engineering and Sciences, 2025)
An automatic Voltage Regulator (AVR) maintains a constant terminal voltage by adjusting the field current of the generator. It may respond more slowly to correcting small changes in voltage. This slower response can affect the equipment which are highly sensitive to minor voltage variations. So, an additional piece of equipment, a Power System Stabilizer (PSS), is used to enhance overall stability by damping oscillations, along with AVRs. There is a need for advancements in PSS design to improve reliability and enhance stability performance. The study of Automatic Voltage Regulator (AVR) and Power System Stabilizer (PSS) coordination with two controllers, a Lead-Lag compensator and a Proportional-Integral-Derivative (PID) controller, is carried out. Three-phase ground fault and load variations (an additional 10MW and 50 MVAR) were introduced into the system to evaluate performance. Evaluation was based on key performance metrics such as settling time, overshoot, undershoot, and damping ratio. The AVR without PSS showed poor performance, emphasizing the necessity of supplementary stabilization. Utilizing the robust capabilities of MATLAB-SIMULINK, the PID controller was finely tuned. PID-based PSS outperformed the others, achieving the fastest settling time and the highest damping ratio. The PSS with conventional lead-lag in MATLAB-SIMULINK exhibited higher overshoot and instability risks. This detailed evaluation confirms the PID controller's superiority over the traditional PSS system. These results were compared with other published research papers, further validating the superior performance of the PID controller. This paper helps researchers evaluate the performance of AVR with PSS and select a better controller to achieve better performance.